The Red Pyramid (The Kane Chronicles #1) - Rick Riordan (Great Britain Puffin Books, 2010)
I guess it started the night our Dad blew up the British Museum... Carter and Sadie Kane's dad is brilliant Egyptologist with a secret plan that goes horribly wrong. An explosion shatters the ancient Rosetta Stone and unleashes Set, the evil god of chaos... Set imprisons Dr Kane is a golden coffin, and Carter and Sadie are forced to run for their lives. To save their dad, they must embark on a terrifying quest from Cairo and Paris to the American South-west and discover the truth about their family's connection to the House of Life: an Egyptian temple of magic that has existed for thousands of years. The pharaohs of ancient Egypt are far from dead and buried. And so, unfortunately are their gods...
Keywords: Fantasy; Urban fantasy; Young Adult; Childrens; Fiction; Magic; Mythology